Michael Harney, Kinship and polity in the "Poema de mio Cid". Purdue University Press, West Lafayette, IN, 1993; 285 pp. (Puerdue studies in Romance literatures, 2). - Higashi, Alejandro (Nueva Revista de Filología Hispánica (NRFH), 1995)
Se reseñó el libro: Kinship and polity in the "Poema de mio Cid".